Characteristics and Microstructure of Geopolymer Mortars incorporating Ground Granulated Blast Furnace Slag and Calcined Dolomite Powder: A Sustainable Solution for Construction Materials - Shaaban, Mostafa; Hussien, Omnia Farouk; Khalifa, Safinaz (Engineering, Technology & Applied Science Research, 2025)
The global demand for environmentally sustainable and cost-effective materials that reduce carbon emissions and energy consumption has significantly risen. In this context, geopolymer binders, primarily sourced from industrial by-products or agricultural waste, have emerged as viable alternatives to traditional Ordinary Portland Cement (OPC). This study examines the characteristics and microstructure of two types of geopolymer mortars: one utilizing an alumina-rich binder, namely calcined clay, and the other employing a silica-rich binder, namely rice husk ash. Both mortar types incorporate a consistent 30% Ground Granulated Blast Furnace Slag (GGBFS), with Calcined Dolomite Powder (CDP) added in varying proportions of 10%, 15%, 20%, and 25%. A total of eight geopolymer mortar mixes, along with a reference mix consisting of 100% OPC, were prepared and evaluated for setting time, flowability, compressive strength, flexural strength, and dry density. Additionally, microstructural analysis was conducted using electron microscopy techniques. The results indicated that the clay-based geopolymer mortars outperformed those based on rice husk ash. Notably, the mixes containing 30% GGBFS, 50% calcined clay, and 20% calcined dolomite powder, as well as those with 30% GGBFS, 45% calcined clay, and 25% calcined dolomite powder, exhibited performance levels comparable to, or slightly exceeding, those of the reference mix.